Effects of sex, age, and visits on receipt of preventive healthcare services: a secondary analysis of national data - Garrett Joanne M; Thorpe Joshua M; Viera Anthony J (BMC, 2006)
Abstract Background Sex and age may exert a combined influence on receipt of preventive services with differences due to number of ambulatory care visits. Methods We used nationally representative data to determine weighted percentages and adjusted odds ratios of men and women stratified by age group who received selected preventive services. The presence of interaction between sex and age group was tested using adjusted models and retested after adding number of visits. Results Men were less likely than women to have received blood pressure screening (aOR 0.44;0.40-0.50), cholesterol screening (aOR 0.72;0.65-0.79), tobacco cessation counseling (aOR 0.66;0.55-0.78), and checkups (aOR 0.53;0.49-0.57). In younger age groups, men were particularly less likely than women to have received these services. In adjusted models, this observed interaction between sex and age group persisted only for blood pressure measurement (p = .016) and routine checkups (p < .001). When adjusting for number of visits, the interaction of age on receipt of blood pressure checks was mitigated but men were still overall less likely to receive the service. Conclusion Men are significantly less likely than women to receive certain preventive services, and younger men even more so. Some of this discrepancy is secondary to a difference in number of ambulatory care visits.